Implementasi Nilai-Nilai Karakter Islami dalam Pembelajaran Pendidikan Agama Islam - Edi Prayitno (UIN Fatmawati Sukarno Bengkulu, 2022)
The problem in this research is How is the implementation of Character Education in Islamic Education Learning in SMA Negeri 2 Muara Beliti Musi Rawas? What are the obstacles faced by teachers in the process of implementing character education in learning Islamic Religious Education at SMA Negeri 2 Reference Muara Beliti Musi Rawas ?. The research can draw the following conclusions: First, the perceptions of PAI teachers at SMA Negeri 2 Unggulan Muara Beliti on the implementation of character education and the role of Islamic education learning in character building is very positive. Second, the Implementation of Character Education in PAI Learning at Muara Beliti 2 Referral High Schools is applied with a strategy of value analysis, value clarification, exemplary stories, and cooperative learning models. Meanwhile, the habituation that is carried out is praying before starting and after learning, shaking hands when meeting the teacher, on time, and memorizing. Third, there are several obstacles in the implementation of character education, there are four obstacles faced by Islamic Education teachers, namely: a) lack of facilities and a forum for student development; 2) weak synergy of various elements, especially parents and society; 3) the environment is not conducive; and 4) character that is hard / difficult to manage.